CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF MEASLES IN THE SAMARKAND REGION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Measles remains a significant public health challenge because of its extremely high contagiousness, ability to spread rapidly, and susceptibility of all age groups. International specialists emphasize that elimination of the measles virus is achievable through extensive vaccination programs. The primary contributing factors to the growing number of measles cases include gaps in vaccination coverage related to population migration, delayed identification of the disease, and the absence of timely anti-epidemic interventions.